2018
DOI: 10.25301/jpda.274.181
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Status Among Hearing and Speech Impaired Children of Karachi, Pakistan

Abstract: To evaluate dental status of children with hearing and speech impairment of Karachi Pakistan. METHODOLOGY: This cross sectional study was conducted in Karachi, Pakistan for a period of 6 month among 106 children with hearing and speech impairment aged 5-15 years of either gender attending Deaf Reach School. After taking informed consent the subjects were examined for oral health status. Dental caries was assessed by using DMFT index and Oral hygiene status was assessed by using oral hygiene index simplified (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…40 A low prevalence of poor oral health status among hearing-impaired children in Nigeria (22.2%) 41 and Pakistan (5.7%). 12 Moreover, the current study found a significant association between poor oral hygiene status and dental caries. Recently, Vichayanrat et al reported that hearing-impaired college students in Thailand with poor oral hygiene status were 3.26 times more likely to have dental caries (OR 3.26; 95% CI: 1.64–6.45) than those with good oral hygiene status.…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…40 A low prevalence of poor oral health status among hearing-impaired children in Nigeria (22.2%) 41 and Pakistan (5.7%). 12 Moreover, the current study found a significant association between poor oral hygiene status and dental caries. Recently, Vichayanrat et al reported that hearing-impaired college students in Thailand with poor oral hygiene status were 3.26 times more likely to have dental caries (OR 3.26; 95% CI: 1.64–6.45) than those with good oral hygiene status.…”
Section: Discussionsupporting
confidence: 49%
“… 37 Azfar et al reported that over half (51%) of hearing and speech-impaired children in Pakistan had dental caries. 12 Moreover, a much higher rate of dental caries was reported among hearing-impaired college students in Thailand (82.5%) 36 and Saudi Arabia (82.2%). 38 The difference might be due to socioeconomic variation between the study participants, and the difference in public welfare for the disabled population among countries.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations